Personality and social foraging tactic use in free-living Eurasian tree sparrows (Passer montanus). (12th March 2019) - Fülöp, Attila; Németh, Zoltán; Kocsis, Bianka; Deák-Molnár, Bettina; Bozsoky, Tímea; Barta, Zoltán
Abstract: Group-foraging individuals often use alternative behavioral tactics to acquire food: some individuals, the producers, actively search for food, whereas others, the scroungers, look for opportunities to exploit the finders' discoveries. Although the use of social foraging tactics is partly flexible, yet some individuals tend to produce more, whereas others largely prefer to scrounge. This between-individual variation in tactic use closely resembles the phenomenon of animal personality; however, the connection between personality and social foraging tactic use has rarely been investigated in wild animals. Here, we studied this relationship in free-living Eurasian tree sparrows ( Passer montanus ) during 2 winters. We found that in females, but not in males, social foraging tactic use was predicted by personality: more exploratory (i.e., more active in a novel environment) females scrounged more. Regardless of sex, the probability of scrounging increased with the density of individuals foraging on feeders and the time of feeding within a foraging bout, that is, the later the individual foraged within a foraging bout the higher the probability of scrounging was. Our results demonstrate that consistent individual behavioral differences are linked, in a sex-dependent manner, to group-level processes in the context of social foraging in free-living tree sparrows, suggesting that individual behavioral traits have implications for social evolution. Abstract : We show that more exploratory female, but not male, Eurasian tree sparrows scrounge more during social foraging. While foraging in groups, individuals either search for food themselves (the producers), or join other group members and exploit their finds (the scroungers). Using the producing or scrounging foraging tactic during social foraging might depend on the personality of individuals in a sex-dependent way. However, this relationship has been rarely studied in free-living animals.